The Sedimentary records of the Hapcheon impact crater basin in Korea over the past 1.3 Ma - Lee, Jin-Young; Shin, Seungwon; Yoon, Hyun Ho; Kim, Jin Cheul; Choi, Yire; Nahm, Wook-Hyun; Kim, Heejung (Frontiers in Earth Science, 2023)
The Hapcheon impact crater is the only meteorite impact crater identified on the Korean peninsula. However, the morphology of the impact crater and the nature of the meteorite collision are unknown. In this study, we analyzed the sedimentary facies using grain size data; computed tomography images, 14C, 10Be, and optically stimulated luminescence dating on a >66-m-long sediment core (20HCL04) recovered from the Hapcheon Basin. Four sedimentary units and 10 types of facies were documented in the Hapcheon Basin sediment core. The sedimentary units comprise 1) a lower part (unit 1) that is dominated by moderately to well-sorted coarse gravel, which contains some impact-related sediments; 2) a middle part (units 2 and 3) dominated by well-laminated mud; and 3) an upper part (Unit 4) that is dominated by poorly sorted coarse gravel supplied from the surrounding mountain slopes by alluvial and fluvial processes. After the meteorite impact, the Hapcheon impact crater was filled with deposits from the crater wall after ca. 1.3 Ma and the Hapcheon Basin became a deep lake environment. After ca. 0.5 Ma, sediments were supplied from the surrounding mountains until the lake was filled. Finally, sediments were deposited in an alluvial fan setting. In addition, the Hapcheon Basin sedimentary cores contain a tephra layer and deformed soft sediments that can be used to investigate volcanic and seismic events on the Korean Peninsula over the past 1.3 Ma.